Muon spin rotation and relaxation study on topological noncentrosymmetric superconductor PbTaSe2. (31st January 2022) - Zhu, Z H; Tan, C; Zhang, J; Biswas, P K; Hillier, A D; Wang, M X; Yang, Y X; Chen, C S; Ding, Z F; Li, S Y; Shu, L
Abstract: Topological superconductivity is an exotic phenomenon due to the symmetry-protected topological surface state, in which a quantum system has an energy gap in the bulk but supports gapless excitations confined to its boundary. Symmetries including central and time-reversal symmetry (TRS), along with their relations with topology, are crucial for topological superconductivity. We report muon spin relaxation/rotation ( μ SR) experiments on a topological noncentrosymmetric superconductor PbTaSe2 to study its TRS and gap symmetry. Zero-field μ SR experiments indicate the absence of internal magnetic field in the superconducting state, consistent with previous μ SR results. Furthermore, transverse-field μ SR measurements reveals that the superconducting gap of PbTaSe2 is an isotropic three-dimensional fully-gapped single-band. The fully-gapped results can help understand the pairing mechanism and further classify the topological superconductivity in this system.